Evaluation of the Independent Science and Partnership Council (ISPC) - Pehu, Eija; O’Kane, Mary (CGIAR Independent Evaluation Arrangement, 2017)
The Independent Science and Partnership Council (ISPC) is an independent scientific advisory body of the CGIAR. It was formally constituted in January 2011, in response to the 2008 CGIAR Reform that called for changes to the CGIAR Science Council, which was the science advisory body at the time. The ISPC was to provide independent scientific advice and expertise to the CGIAR Fund Council (now System Council), to serve as an intellectual bridge between CGIAR funders and implementers, and to catalyze partnerships with other international agricultural research institution. The main purposes of the evaluation are twofold:1) to provide accountability to System Council and CGIAR as a whole on the relevance and overall performance of the ISPC with respect to all dimensions of the ISPC’s functions and work and 2) to draw lessons and make recommendations for the future, with a view for the ISPC to best serve the System Council and CGIAR as a whole in the context of the governance reform and the implementation of the Strategic and Results Framework 2016-30 (SRF 2016-2030). The evaluation will cover all activities of the ISPC since its establishment in 2011 taking into account a historical perspective, when appropriate, with a view to understanding how the System’s needs for scientific advice have evolved over time. The evaluation will assess the relevance and scope of the leadership and advisory functions as well as of the work of the ISPC; the operational and functional performance of the ISPC as a whole and in its areas of activity; and the value it adds to other actors in the System that have similar functions at different levels.